Машина: повесть / Анатолий Андреев - Андреев Анатолий Александрович (Удмуртия, 1988)
Экземпляры: Ф4; ф8; ф12; ф13 (20221118ԁ) / Инвентарный номер: 19362 / Цена: 0.55 / Сис.шифр: Р2 / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6